Organization and Unconventional Integration of the Mating-Type Loci in Morchella Species - Hongmei Chai; Ping Liu; Yuanhao Ma; Weimin Chen; Nan Tao; Yongchang Zhao (Journal of Fungi, 2022)
True morels (Morchella spp.) are a group of delicious fungi in high demand worldwide, and some species of morels have been successfully cultivated in recent years. To better understand the sexual reproductive mechanisms of these fungi, we characterized the structure of the mating-type loci from ten morel species, and seven of them were obtained using long-range PCR amplification. Among the studied species, eight were heterothallic, two were homothallic, and four types of composition were observed in the MAT loci. In three of the five black morel species, the MAT1-1-1, MAT1-1-10, and MAT1-1-11 genes were in the MAT1-1 idiomorph, and only the MAT1-2-1 gene was in the MAT1-2 idiomorph, while an integration event occurred in the other two species and resulted in the importation of the MAT1-1-11 gene into the MAT1-2 idiomorph and survival as a truncated fragment in the MAT1-1 idiomorph. However, the MAT1-1-11 gene was not available in the four yellow morels and one blushing morel species. M. rufobrunnea, a representative species of the earliest diverging branch of true morels, along with another yellow morel Mes-15, were confirmed to be homothallic, and the MAT1-1-1, MAT1-1-10, and MAT1-2-1 genes were arranged in a tandem array. Therefore, we hypothesized that homothallism should be the ancestral reproductive state in Morchella. RT-PCR analyses revealed that four mating genes could be constitutively expressed, while the MAT1-1-10 gene underwent alternative splicing to produce different splice variants.